Belenggu Hegemoni Patriarki dalam Cerpen Bulan Kuning Sudah Tenggelam Karya Ahmad Tohari - Lestari, Selvi Triana; Rabbani, Ilham (Universitas Ahmad Dahlan, 2023)
This research seeks to dismantle the fetter of patriarchal hegemony and resistance carried out by female characters in the short story Bulan Kuning Sudah Tenggelam by Ahmad Tohari. Gramsci's theory of hegemony and Walby's thoughts on patriarchy are used as analytical tools. The method used is qualitative-descriptive. The findings of this research: The fetter of patriarchal hegemony experienced by Yuning's character occurs because of the hierarchical relationship between her and Raden Barnas as her father and his wife in the family structure. In truth, Yuning has shown resistance to the fetters she has experienced. However, it is anti-climatic because of the forgiveness of her husband's infidelity. At the same time, this condition marks the position of Yuning's figure being re-fettered by patriarchal hegemony, both in the family system and in the order of a country.